Development of A Collaborative Business Planning Model for Metal SMEs In Sukabumi District - Raden Muhammad Rizaldi Hardjakoesoemah; Dwi Kurniawan (Yayasan Ghalih Pelopor Pendidikan, 2025)
Increasing business competition necessitates innovative approaches to strategic planning, particularly among small and medium-sized enterprises (SMEs). This study introduces the Collaborative Business Planning (CBP) model, which differs from conventional approaches by embedding collaboration through synergy, transparency, and shared responsibility among business group members. Using a simplified Delphi method, consensus was obtained from experts and practitioners to identify key collaboration factors, design the CBP framework, and validate its structure. The model integrates expert consensus, strategic planning, and financial feasibility analysis to produce a comprehensive planning tool for business groups. Implementation of the CBP model in KUB Mandiri Bersinergi demonstrated substantial improvements in performance and cooperation. Financial assessments revealed a positive Net Present Value (NPV) and an Internal Rate of Return (IRR) exceeding 20 percent, confirming its economic viability. The study contributes a structured framework for strengthening collaboration, enhancing efficiency, and promoting sustainability within SMEs. The CBP model provides both a theoretical and practical foundation for collective business planning, offering strategic guidance for SMEs to manage collaboration effectively and achieve long-term competitive advantage.